2021
DOI: 10.3389/fsurg.2021.719226
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Serum Albumin Level on Admission in Patients With Spontaneous Subarachnoid Hemorrhage

Abstract: Objective: To determine the effect of the serum albumin level on admission in patients with spontaneous subarachnoid hemorrhage (SAH).Methods: A total of 229 patients with SAH were divided into control and hypoalbuminemia groups. The serum albumin levels were measured. The data, including age, gender, co-existing medical conditions, risk factors, Hunt-Hess (H-H) grade on admission, Glasgow coma score (GCS) on admission, complications during hospitalizations, length of hospital stay, length of intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…Hypoalbuminemia are common in patients with aSAH and are independently associated with a poor prognosis [5].Similarly, we had observed a negative correlation between albumin concentration and clinical outcome, which was in consistent with former studies [11,12]. Hypoproteinemia in patients with aSAH may be caused by systemic in ammation, malnutrition and active catabolic metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Hypoalbuminemia are common in patients with aSAH and are independently associated with a poor prognosis [5].Similarly, we had observed a negative correlation between albumin concentration and clinical outcome, which was in consistent with former studies [11,12]. Hypoproteinemia in patients with aSAH may be caused by systemic in ammation, malnutrition and active catabolic metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Induction of hyperglycemia in rats led to augmented neuronal apoptosis 12 and 24 hours after ICH, which was accompanied by a reduction in albumin and other DEPs. 49 Low serum albumin levels were associated with poor functional outcome in patients with SAH, ICH, and IS [50][51][52] by increasing Datasets were derived from the following studies: ischemia, 4-26 intracerebral hemorrhage (ICH). 6,[27][28][29][30] Only DEPs that were identified in at least 2 proteomics studies were considered for analysis (Table S3, n=293 for ischemia and n=47 for ICH).…”
Section: Stroke and Neurocognitive Impairment Compendiummentioning
confidence: 99%
“…Rass et al (1) substantiate the inclusion of the APS owing to a likely systemic inflammatory response post-SAH wherein the lack of account of the concomitant serum albumin levels draws peculiar attention, appropriate to the aforementioned context (1). Ahead of the inflammatory association of hypoalbuminemia, the latter entails dose-dependent poor clinical outcomes in the critically ill (2). Even from a strict neurocritical perspective, Shang et al (2) in a retrospective study of 229 patients demonstrated a higher predilection for intubation, pneumonia and cerebral vasospasm, in the SAH subset with hypoalbuminemia ( n = 150) in comparison to the subset with normoalbuminemia ( n = 79) (43.6% vs 8.9%, p < 0.001; 46.3% vs 13.9%, p < 0.001; 50.7% vs 32.9%, p = 0.010, respectively).…”
Section: To the Editormentioning
confidence: 99%
“…Ahead of the inflammatory association of hypoalbuminemia, the latter entails dose-dependent poor clinical outcomes in the critically ill (2). Even from a strict neurocritical perspective, Shang et al (2) in a retrospective study of 229 patients demonstrated a higher predilection for intubation, pneumonia and cerebral vasospasm, in the SAH subset with hypoalbuminemia ( n = 150) in comparison to the subset with normoalbuminemia ( n = 79) (43.6% vs 8.9%, p < 0.001; 46.3% vs 13.9%, p < 0.001; 50.7% vs 32.9%, p = 0.010, respectively). This translated as a protracted length of stay-ICU (LOS-ICU) and length of stay-hospital in their patients with hypoalbuminemia (2).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation